Identity is an endless, ever-unfinished conversation": Stuart Hall's Legacy and the Polyphonic Memories of the Black Diaspora in John Akomfrah's Works - Paola Valenti (Cinergie, 2019)
Since the early Eighties, and up until this day, the Ghanaian born artist, film and video-maker John Akomfrah sets out to intervene in the cultural debate raging all over Britain about black identity and its representation.  As a member of the London based Black Audio Film Collective (BAFC), and later in his solo career, Akomfrah creates a counter-narrative around the gap between the dominant discourses on ethnicity and “Britishness” and what was, and is, intimately felt and experienced by the so-called “post-migrants”. Taking Stuart Hall’s statement quoted in the title as a visual enactment, and referring to his theoretical work as well as to his biography, the essay will mainly focus on a trilogy of works that has a direct connection with the legacy of this seminal figure – Handworth Songs (Akomfrah, 1986), The Nine Muses (Akomfrah, 2011), The Unfinished Conversation (Akomfrah, 2012) – and witnesses to the creation of postcolonial black subjectivity intermingling eye-witness accounts, memories, domestic pictures of individuals and families, newspaper images,  archival and newly staged footage in a poetic montage of still and moving images, in an affective interplay of multiple sonic textures, in a non-linear temporality in which past, present and future continuously overlap.